Multistate Analysis of Time Consumption in Capital Appeals, 1992-2002 - Latzer, Barry ([Verlag nicht ermittelbar], 2008)
Despite public controversy over the length of death penalty appeals, little empirical work has been done on the time allocated to the capital appeals process. The purpose of this study was to perform a multistate empirical analysis of the time expended in direct appeals of capital cases. The researchers included decisions from 14 states that they believed to be representative of the 37 states that have enforceable death penalty laws. For each of the 14 states included in the study, the researchers examined every capital case decided on direct appeal by the courts of last resort between the dates January 1, 1992, and December 31, 2002. The researchers developed a case database by examining a variety of sources. For each of the 1,676 cases in the multistate database, the research team collected time consumption data for each of the following five phases of the direct appeal process: (1) the postsentence stage, (2) the preparation stage, (3) the argument stage, (4) the decision stage, and (5) the supreme court stage. Variables include state, case characteristics, court opinion variables, dates, and time consumption variables.